2023
DOI: 10.2478/jesm-2023-0001
|View full text |Cite
|
Sign up to set email alerts
|

From the Consumers’ Side: Determining Students’ Perception and Intention to Use ChatGPT in Ghanaian Higher Education

Abstract: The advent and development of technologies such as artificial intelligence have created benefits and challenges for educational stakeholders. Artificial intelligence, such as OpenAI’s Chat Generative Pre-trained Transformer (ChatGPT), has brought new benefits, challenges and pressures for higher educational institutions. There are relatively few reports of how students perceive and intend to use ChatGPT. Taking cognizance of these, the research explored students’ perceptions and intentions to use ChatGPT in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
17

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 55 publications
4
14
0
17
Order By: Relevance
“…Results revealed that two-thirds of the participants believed that ChatGPT offers them benefits, especially in the identification of treatment-related problems, drug-drug interactions, and adverse drug reactions participants. Many other applications of ChatGPT were studied, such as differential diagnosis, 16 clinical decision-making, 17 and clinical decision support. 16 The perceived benefits of incorporating ChatGPT in education were echoed in a mixed-method approach study conducted in Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results revealed that two-thirds of the participants believed that ChatGPT offers them benefits, especially in the identification of treatment-related problems, drug-drug interactions, and adverse drug reactions participants. Many other applications of ChatGPT were studied, such as differential diagnosis, 16 clinical decision-making, 17 and clinical decision support. 16 The perceived benefits of incorporating ChatGPT in education were echoed in a mixed-method approach study conducted in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers recommended adopting these innovative technologies in higher education accompanied by regulatory measures concerning ethical challenges such as creativity, misuse, and copyright issues. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, both purposive and convenience sampling techniques were used in this study, as was customary for comparable research. 47 Purposive sampling was used for selecting participants based on their characteristics, knowledge, experiences such as “affecting from mental health problems” and has “awareness of using ChatGPT”; and convenience sampling was used to recruit individuals who can be easily accessed, ie, from university hospital. When approximately 42 adult patients were initially asked if they were interested in participating in the study, 35 responded positively.…”
Section: Methodsmentioning
confidence: 99%
“…However, the sheer complexity and scale of these models present challenges in terms of explainability [551], [552]. As LLMs continue to grow in size, with models containing billions of parameters, the ability to comprehensively explain their decision-making processes becomes increasingly elusive [553], [554]. This complexity makes it exceedingly difficult for humans to understand and interpret the decision-making mechanisms employed by the model [85].…”
Section: H Risks Of Foundation Modelsmentioning
confidence: 99%